Stimuli-Responsive Biomass Cellulose Particles Being Able to Reversibly Self-Assemble at Fluid Interface - Zhu, Yue; Chen, Tingting; Cui, Zhenggang; Dai, Hong; Cai, Li (Frontiers in Chemistry, 2020)
Stimuli-responsive surface-active microcrystalline cellulose (MCC) particles are obtained by interaction with conventional cationic surfactants such as cetyltrimethylammonium bromide (CTAB) in aqueous media, where MCC are in situ hydrophobized by adsorption of the cationic surfactant in water via electrostatic interaction and with the in situ hydrophobization removed by adding an equimolar amount of an anionic surfactant such as sodium dodecyl sulfate (SDS). The trigger is that the electrostatic interaction between the oppositely charged ionic surfactants is stronger than that between the cationic surfactant and the negative charges on particle surfaces, or the anionic surfactant prefers to form ion pairs with the cationic surfactants and thus making them desorbed from surface of MCC. Reversible O/W Pickering emulsions can then be obtained by using the MCC in combination with trace amount of a cationic surfactant and an anionic surfactant, and the anionic surfactant with a longer alkyl chain is more efficient for demulsification. With excellent biocompatibility, biodegradability, and renewability, as well as low toxicity, the biomass cellulose particles that can be made stimuli-responsive and able to reversibly self-assemble at fluid interface become ideal biocompatible particulate materials with extensive applications involving emulsions and foams.